Transforming Provincial Politics : The Political Economy of Canada's Provinces and Territories in the Neoliberal Era - Smith, Charles W., 1976-; Evans, Bryan M., 1960- (Book collections on Project MUSE., 2015)
Transforming Provincial Politics is the first province-by-province analysis of politics and political economy in more than a decade, and the first to directly examine the turn to neoliberal policies at the provincial and territorial level.